2018
DOI: 10.1038/s41598-018-32747-x
|View full text |Cite
|
Sign up to set email alerts
|

First insight into microbiome profile of fungivorous thrips Hoplothrips carpathicus (Insecta: Thysanoptera) at different developmental stages: molecular evidence of Wolbachia endosymbiosis

Abstract: Insects’ exoskeleton, gut, hemocoel, and cells are colonized by various microorganisms that often play important roles in their host life. Moreover, insects are frequently infected by vertically transmitted symbionts that can manipulate their reproduction. The aims of this study were the characterization of bacterial communities of four developmental stages of the fungivorous species Hoplothrips carpathicus (Thysanoptera: Phlaeothripidae), verification of the presence of Wolbachia, in silico prediction of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 132 publications
(123 reference statements)
8
21
0
Order By: Relevance
“…Colman, Toolson & Takacs-Vesbach, 2012;Jones, Sanchez & Fierer, 2013;Yun et al, 2014;Kim et al, 2017), and also in those cultivating fungi (Aylward et al, 2014). Moreover, identified patterns of the abundance remained in congruence with the results of our previous study focused on microbial communities associated with Hoplothrips carpathicus (Thysanoptera), which also inhabits fruiting bodies of F. fomentarius (Kaczmarczyk et al, 2018). Interestingly, at the genus level Burkholderia-Cabalerrinia-Paraburkholderia (Burkholderiaceae) was one of the most dominant genera in all tested samples.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 85%
See 2 more Smart Citations
“…Colman, Toolson & Takacs-Vesbach, 2012;Jones, Sanchez & Fierer, 2013;Yun et al, 2014;Kim et al, 2017), and also in those cultivating fungi (Aylward et al, 2014). Moreover, identified patterns of the abundance remained in congruence with the results of our previous study focused on microbial communities associated with Hoplothrips carpathicus (Thysanoptera), which also inhabits fruiting bodies of F. fomentarius (Kaczmarczyk et al, 2018). Interestingly, at the genus level Burkholderia-Cabalerrinia-Paraburkholderia (Burkholderiaceae) was one of the most dominant genera in all tested samples.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 85%
“…Manuscript to be reviewed with F. fomentarius feeding species remain exposed to these compounds. Moreover, the similar pattern of relative abundances were identified for predicted genes in the case of bacterial communities associated with thrips H. carpathicus (Kaczmarczyk et al, 2018). This might mean that similarities in predicted patterns of relative abundances of genes are characteristic for bacterial communities associated with fungivorous species inhabiting fruiting bodies of wooddecaying fungi.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 54%
See 1 more Smart Citation
“…These common bacterial members were consistent with previous reports that Proteobacteria and Bacteroidetes were discovered as indigenous bacteria in juvenile shrimp [7][8][9] . Analysis of bacterial communities in growth developmental stages of human 4,48 and thysanoptera 49 revealed that the bacterial communities could be formed since the early life stages until they fully developed into adults, and continued to modulate the host's immune system and enhance the protection against pathogen colonization and infection 50 . However, the host-bacteria interactions in P. monodon still require a much further investigation to obtain a better understanding of their relationships and potential benefits to the animal host.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings related to the insect gut microbiome have shown that it generally harbors a lower microbial diversity as compared to the mammalian guts (Engel and Moran, 2013). The most abundant phyla in various insect species were shown to be Proteobacteria and Firmicutes (Alonso-Pernas et al, 2017;Kaczmarczyk et al, 2018;van Schooten et al, 2018). Similar to other organisms, the insect-associated microbial communities generally show differences across the life stages of their hosts (Alonso-Pernas et al, 2017;Kaczmarczyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%